2017
DOI: 10.1038/mp.2017.128
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine for suicidality: from universality to subtypes and personalization

Abstract: Suicide remains a clear, present and increasing public health problem, despite being a potentially preventable tragedy. Its incidence is particularly high in people with overt or un(der)diagnosed psychiatric disorders. Objective and precise identification of individuals at risk, ways of monitoring response to treatments and novel preventive therapeutics need to be discovered, employed and widely deployed. We sought to investigate whether blood gene expression biomarkers for suicide (that is, a ‘liquid biopsy’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 65 publications
(48 reference statements)
3
60
0
Order By: Relevance
“…Among the best known is the Beck Depression Inventory, a self-report rating tool that contains 21 questions and has been used in a variety of settings. 37 More recently, personalized approaches to suicidality have been suggested with the description of relevant biomarkers, 38 which may assist in better risk stratification and assessment of the response to treatment. The results of this study demonstrate that screening for depression would especially be indicated during the first year after diagnosis, where the risk for committing suicide was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Among the best known is the Beck Depression Inventory, a self-report rating tool that contains 21 questions and has been used in a variety of settings. 37 More recently, personalized approaches to suicidality have been suggested with the description of relevant biomarkers, 38 which may assist in better risk stratification and assessment of the response to treatment. The results of this study demonstrate that screening for depression would especially be indicated during the first year after diagnosis, where the risk for committing suicide was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray work was carried out using previously described methodology [7][8][9][10]. The dataset is available at GEO (GSE127711).…”
Section: Microarraysmentioning
confidence: 99%
“…This was done in order to normalize and be able to easily combine internal (discovery) and external evidence (prioiritzation) scores, and to avoid over-fitting to the discovery cohort. We have developed in our lab R scripts to automate and conduct all these large dataset analyses in bulk, checked against human manual scoring [10].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although suicide research has made many advances [1], suicide remains an unpredictable [2] but leading cause of death. There are many known indicators/risk factors that can alert physicians' of those at risk of suicide, including clinical (e.g., psychiatric illness, substance use, previous attempts, medical illness), demographic (e.g., male sex, older age, living alone), genetic, and psychological (e.g., unemployment, interpersonal conflict) factors.…”
Section: Introductionmentioning
confidence: 99%